Kompresi File Teks dengan Menggunakan Kombinasi Squitur dan Elias Gamma Code - Tulus Fransius Silaban (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Text files have a large size that affects the storage space and the sending process. This size is a factor in how much storage space will be used and how long it will take to send files. The longer the text, the larger the size. Large sizes can be overcome by doing the compression process. Compression is done to reduce the size of a file. Compression algorithms that can be used are sequitur algorithm and elias gamma code algorithm. The advantage of the sequitur algorithm is to replace 2 characters side by side with 1 terminal character in the character set, while the advantage of the elias gamma code algorithm is to replace the initial bit of the character with a gamma elias code bit. The two algorithms will be combined to produce a smaller size than the previous one